Journal of South Asian Languages and Linguistics (De Gruyter Mouton, 2014)
The journal provides a peer-reviewed forum for publishing original research articles and reviews in the field of South Asian languages and linguistics, with a focus on descriptive, functional and typological investigations. Descriptive analyses are encouraged to the extent that they present analyses of lesser-known languages, based on original fieldwork. Other areas covered by the journal include language change and sociolinguistics.